Analisis Kadar Kurkumin Pada Jamu Kunyit Asam Dengan Metode Spektrofotometri Visibel - Ayunita, Fidiya; Hidayatullah, Muhammad Haqqi (Journal of Pharmaceutical and Sciences, 2026)
The rhizome of turmeric (Curcuma longa L.) contains curcumin as the principal bioactive compound responsible for its diverse pharmacological activities. Therefore, the analysis of curcumin content is essential for the quality control of herbal medicines. This study aimed to determine the curcumin content in five turmeric herbal medicine samples obtained from herbal vendors in the Kartasura area. Thin-layer chromatography (TLC) was employed for qualitative identification, while visible spectrophotometry was used for quantitative analysis. Samples were selected using purposive sampling and extracted with chloroform, followed by evaporation using a water bath and reconstitution in 96% ethanol. Quantitative analysis was performed by measuring curcumin content on days 1, 2, and 3 of storage to evaluate content stability. Qualitative TLC analysis was conducted using silica gel 60 F254 as the stationary phase and a mobile phase consisting of ethanol, glacial acetic acid, and chloroform (94:5:1, v/v/v). The TLC results confirmed the presence of three curcuminoid compounds curcumin, demethoxycurcumin, and bisdemethoxycurcumin with consistent Rf values observed under UV light at 254 nm and 366 nm. Quantitative analysis using visible spectrophotometry showed significant differences in curcumin content among samples (p < 0.001) based on one-way ANOVA. Method validation demonstrated excellent linearity (R² = 0.9995), acceptable accuracy (mean recovery of 109.67%), good precision (RSD of 1.80%), and sensitivity with LOD and LOQ values of 0.128 ppm and 0.388 ppm, respectively. These findings indicate that the validated spectrophotometric method is suitable for determining curcumin content in turmeric-based herbal medicines. Variations in curcumin levels among samples may be attributed to differences in raw material quality and manufacturing processes.